The Arborigram. Didactic strategy of reading comprehension of narrative texts - Loayza-Maturrano, Edward F. (2021)
The low level of reading comprehension evidenced by basic education students requires proposing proposals that effectively link two socio-educational variables: didactics and reading. The main objective of the research was to determine if there is influence between the arborigram strategy and the improvement of reading comprehension in a pre-adolescent population of the age group of 11 to 13 years of the first grade of the Secondary level in the district of La Molina. A quasi-experimental study was designed that considered a pre-test and post-test regarding the application of the arborigram module. The results indicate the existence of a moderate-high causal influence between the variables of the arborigram strategy and the students' reading comprehension. The main conclusion of the study establishes that the arborigram as a didactic strategy has a significant influence on the improvement of reading comprehension of narrative texts in students of basic education.